The molecular mechanisms by which the NLRP3 inflammasome regulates blood-brain barrier permeability following cryptococcal meningitis - Lingjuan Liu; Yufen Tang; Lu Zhang; Peng Huang; Xingfang Li; Yangyang Xiao; Dingan Mao; Liqun Liu; Jie Xiong (Heliyon)
Objective: To investigate the mechanism underlying the regulation of blood-brain barrier permeability changes during cryptococcal meningitis by NLRP3 and Vimentin. Methods: Sprague-Dawley rats were treated with WT Cryptococcus neoformans (Cn) or CPS1−/− Cn. Neuronal apoptosis was assessed using TUNEL staining, and pathological changes were observed using electron microscopy and HE staining. The expressions of NLRP3, Vimentin, and NF-κB in the cerebral cortex and human brain microvascular endothelial cells (HBMECs) were examined through Western blot and qRT-PCR. siNLRP3 and siVimentin were separately transfected into HBMECs, the expressions of specific factors were assessed. NF-κB and Vimentin levels were detected through immunofluorescence, apoptosis was measured using flow cytometry, and changes in the optical density (OD) of HRP were determined using ELISA. Results: The expressions of NLRP3, Vimentin, and NF-κB were upregulated following intervention with WT Cn in vivo and in vitro. Electron microscopy revealed loose nuclear membranes in neurons and increased apoptosis in the cerebral cortex and hippocampus induced by WT Cn, accompanied by a reduction in the OD of HRP in vitro. siNLRP3 decreased the expressions of Vimentin, nuclear NF-κB, and β-Tubulin in HBMECs, while siVimentin downregulated total NLRP3 and nuclear NF-κB levels. Both siNLRP3 and siVimentin reduced cell apoptosis after WT Cn infection. HBMECs displayed a reduced monolayer permeability to HRP and improved cell structure arrangement. Conclusion: Vimentin and the NLRP3 inflammasome are both implicated in the pathological process of cryptococcal meningitis. An interaction between Vimentin and the NLRP3 inflammasome is evident, likely mediated through the NF-κB signaling pathway.